2020
DOI: 10.1021/acsanm.9b02230
|View full text |Cite
|
Sign up to set email alerts
|

Iridium Oxide Catalyst Supported on Antimony-Doped Tin Oxide for High Oxygen Evolution Reaction Activity in Acidic Media

Abstract: Lowering of the oxygen evolution reaction (OER) noble metal catalyst loading on the anode of a polymer electrolyte membrane water electrolysis (PEMWE) is a necessity for enabling the large-scale hydrogen production based on this technology. This study introduces a remarkably active OER catalyst that is based on the dispersion of Ir nanoparticles on a highly conductive oxide support. The catalyst was designed in a way to combine all characteristics that have been reported to enhance the OER activity on an Ir ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(145 citation statements)
references
References 46 publications
(107 reference statements)
4
141
0
Order By: Relevance
“…These electronic conductivity values are smaller than those reported in literature for thin films or chain-like aggregated TO powders doped with Sb, Nb, or Ta. 33, [36][37][38] The main reason for this is necking between the primary particles as revealed by Senoo et al 36 using the "Necking Index" (the ratio of the specific surface area determined according to the Brunauer-Emmett-Teller model to that estimated from X-ray diffractograms assuming spherical and isolated MTO crystallites). These authors reported that (i) the apparent electronic conductivity of MTO supports increases with decreasing Table S1 of the Supporting Information).…”
Section: Catalystsmentioning
confidence: 99%
“…These electronic conductivity values are smaller than those reported in literature for thin films or chain-like aggregated TO powders doped with Sb, Nb, or Ta. 33, [36][37][38] The main reason for this is necking between the primary particles as revealed by Senoo et al 36 using the "Necking Index" (the ratio of the specific surface area determined according to the Brunauer-Emmett-Teller model to that estimated from X-ray diffractograms assuming spherical and isolated MTO crystallites). These authors reported that (i) the apparent electronic conductivity of MTO supports increases with decreasing Table S1 of the Supporting Information).…”
Section: Catalystsmentioning
confidence: 99%
“…In 2016, Strasser and colleagues 19 have revealed a support-stabilizing effect for the contribution to the corrosion stability of Ir catalyst in acidic water splitting, in which the electronic interaction between catalyst and support can effectively suppress the growth of higher-valent Ir oxides and the subsequent dissolution. The catalyst–support interactions have been investigated on various substrates such as carbon, Ni foam, TiO x , and antimony-doped tin oxide (ATO) 20 24 . However, carbon and Ni can hardly be used in practice, as they would be oxidized at relatively low anodic potentials.…”
Section: Introductionmentioning
confidence: 99%
“…Colloidal approaches are popular to develop Ir-based catalysts. [26][27][28] Typically, these colloidal approaches to prepare supported catalysts consist of two steps, i.e., first the synthesis of colloidal NPs and second their immobilization onto a support material. Here, we compare different surfactant-free colloidal synthesis approaches for the preparation of Ir NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Up to 50 wt.%, the MA achieves values as high as 305 -350 A gIr -1 , whereas "only" 212 A gIr -1 are determined for the Ir/CMeOH 70 wt.% catalyst. It should be stressed that this is still an outstanding performance, considering that state-of-the-art Ir-based catalysts typically exhibit surface areas in the range of 10 -60 m 2 gIr -1 and MA values lower than 200 A gIr -1 even at low Ir loading 27,[42][43][44][45][46][47][48][49]. In the attempt to account for the lower ECSA and MA of EG-based catalysts, we also tested the influence of the flocculation step by comparison of a standard Ir/CMeOH 50 wt.% and Ir/CMeOH, HCl 50 wt.% (see TableS5and FigureS11).…”
mentioning
confidence: 99%